PENGARUH CITRA PERUSAHAAN DAN KEPERCAYAAN TERHADAP KEPUASAN PASIEN PADA RUMAH SAKIT MITRA MEDIKA NAROM KABUPATEN BEKASI - Ajat Sudrajat (Eqien - Jurnal Ekonomi dan Bisnis, 2020)
Patient satisfaction at the hospital is a benchmark that is a benchmark for patients in getting health care. Each hospital must run a variety of strategies so that patients feel satisfied with health services, one of the strategies is through a good corporate image and trust, where a good corporate image can increase trust. So that affecting patient satisfaction Mitra Medika Narom Hospital Kabupaten Bekasi. This research was conducted with descriptive and verification methods, namely knowing, analyzing, explaining and testing hypotheses, and making conclusions and suggestions. The sample in this study amounted to 240 respondents using the Eksplanary Survey method. Data analysis techniques used are ordinal scale techniques and path analysis using the Method of Successive Interval (MSI) tool, Microsoft Excel 2016 computer programs and SPSS 16. The results of this study reveal that the company's image at the Mitra Medika Narom Hospital in Kabupaten Bekasi is in the agreed criteria, meaning that Mitra Medika Narom Hospital has built and made a good company image so that it is better known to all people. Furthermore, trust in Mitra Medika Narom Hospital in Kabupaten Bekasi is in the agreed criteria, meaning that Mitra Medika Narom Hospital has succeeded in building a good and optimal Trust so that patients trust Mitra Medika Narom Hospital to obtain health services. Then the patient satisfaction at the Mitra Medika Narom Hospital in Kabupaten Bekasi is in the agreed criteria, meaning that the patients as respondents feel a high level of satisfaction after completing treatment at the Mitra Medika Narom Hospital. There is a positive, strong and two-way correlation between company image and trust variables of 0.646. There is a partial influence of company image on patient satisfaction at Mitra Medika Narom Hospital significantly by 11.98%. There is a partial influence of trust on patient satisfaction at Mitra Medika Narom Hospital significantly by 25.08%. Then there is a simultan influence of corporate image and trust on patient satisfaction at Mitra Medika Narom Hospital positively and significantly by 37.06% while the remaining 62.94% is contributed by other variables not examined